H5P + AI: A Powerful Combination for Engaging Learning in Open, Distance and Digital Education - Abu Bakar, Shawira; Ahmad Zabidi, Nazrai; Ezdiani Yasin, Nooni (Multidisciplinary Applied Research and Innovation, 2025)
This paper investigates the potential of integrating artificial intelligence with the HyperText Mark-Up Language 5 Package or H5P open-source content creation tool to address the challenge of disengagement and low comprehension in traditional higher education lectures. The purpose of this study is to examine how the synergy between H5P and AI can be harnessed to create more engaging and personalised learning experiences. The problem statement focuses on the need for innovative educational tools that can adapt to diverse learning styles, improve student engagement and outcomes. The key research questions addressed are:How can AI be effectively integrated with H5P to improve interactivity and engagement in higher education. What are the specific benefits and challenges associated with using AI-enhanced H5P content in higher education settings. How do students perceive and respond to AI-powered H5P content compared to traditional learning methods. Through a mixed-methods pilot study, we aim to answer if AI-powered H5P activities can outperform traditional methods in terms of student engagement and learning outcomes. This research delves into the underexplored territory of AI-H5P integration for education, proposing a novel approach to create personalised and engaging learning experiences. This innovative approach has demonstrated compelling findings, including significant improvements in student engagement, retention, and academic performance. Interactiveness is also rated highly with 69% students storngly agree that graphics and illustrations of H5P materials are interactive. Students reported higher satisfaction with 96% of respondents either satisfied or very satisfied with AI-powered H5P content, highlighting the potential for AI to transform educational experiences. This research can inform future H5P functionalities by highlighting areas where AI integration can be most beneficial. Furthermore, it lays the groundwork for exploring AI-powered H5P’s effectiveness across different disciplines and contexts, while prompting future research to consider the ethical implications of AI in ODDE or open, distance, and digital education setting.